Improvement of Adaptive Load Balanced Gateway Discovery Protocol in Hybrid Integrated Internet-MANET - Zaman, Rafi U; Alam, Humaira M; Khan, Khaleel Ur Rahman; Reddy, A. Venugopal (International Journal of Interactive Mobile Technologies (iJIM), 2017)
Internetworking of different types of networks is envisaged as one of the primary objectives of the future 5G networks. Integrated Internet-MANET is a heterogeneous networking architecture which is the result of interconnecting wired Internet and wireless MANET. Multiprotocol gateways are used to achieve this interconnection. There are two types of Integrated Internet-MANET architectures, two-tier and three-tier. A combination of two-tier and three tier architectures also exists, called the Hybrid Framework or Hybrid Integrated Internet-MANET. Some of the most important issues common to all Integrated Internet-MANET architecture are: efficient gateway discovery, mobile node registration and gateway load balancing. Adaptive WLB-AODV is an existing protocol which addresses the issues of Gateway load balancing and efficient Gateway discovery. In this paper, an improvement is proposed to Adaptive WLB-AODV, called Adaptive Modified-WLV-AODV by taking into account route latency. The proposed protocol has been implemented in Hybrid Integrated Internet-MANET and has been simulated using network simulation tool ns-2. Based on the simulation results, it is observed that the proposed protocol delivers better performance than the existing protocol in terms of performance metrics end-to-end delay and packet loss ratio. The performance of the proposed protocol is further optimized using a genetic algorithm.